The sheep as a pre-clinical model for testing intra-aortic percutaneous mechanical circulatory support devices. Issue 10 (October 2021) - Weisskopf, Miriam; Kron, Mareike; Giering, Tobias; Walker, Tobias; Cesarovic, Nikola
The save deployment of intra-aortic percutaneous mechanical circulatory support devices is highly dependent on the inner aortic diameter. Finding the anatomically and ethically most suitable animal model for performance testing of new pMCS devices remains challenging. For this study, an ovine model using adult ewes of a large framed breed (Swiss White Alpine Sheep) was developed to test safety, reliability, and biocompatibility of catheter-mounted mechanical support devices placed in the descending thoracic aorta. Following the drawback of fluctuating aortic diameter and device malfunction in the first four animals, the model was improved by stenting the following animals with an aortic stent. Stenting the animals with an intra-aortic over the balloon stent was found to standardize the experimental set-up and to avoid early termination of the experiment due to non-device related issues.